Sick bilding symptoms among chidren in private pre-schools in Malaysia: association of different ventilation strategies - Salleh, N.M.; Kamaruzzaman, S.N.; Mahyuddin, N. (Penerbit UKM, 2013)
The health issues among pupils in pre-schools becomes the popular obsession since they are more vulnerable and some indoor environmental quality (IEQ) would be the reason affecting them. Indoor Air Quality (IAQ) in buildings is one of the most important factors affecting the physical development of children. The early education is compulsory and escalated numbers of 4-6 years children has boosted the numbers of private preschool in Malaysia. Frequently it is operate in premises that have been fully refurbished, whether in housing schemes, commercial buildings or institutional buildings. This has invited the questions on the building capability to provide a good environment to the children during the learning activities. Poor indoor air has become a wide-spread problem with serious effects on children health and their performance. This research focuses on identifying occupant satisfaction towards IEQ in selected refurbished pre-school or kindergarten buildings. The broad aim of this paper is to determine SBS among pupils in refurbished private pre-schools with different ventilation strategies and it association with indoor air quality (IAQ) performance. A few parameters have invited several health symptoms to the children and it this is importance of taking into consideration to the owner and policymaker before refurbishing any building into pre-school.